1996
DOI: 10.1002/(sici)1096-9861(19961028)374:4<523::aid-cne4>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic organization of the human striatum: A postmortem ultrastructural study

Abstract: The goal of this study was to characterize the synaptic organization of the normal human adult striatum for comparison with other species and with the diseased human striatum. Samples of striatal tissue from the Maryland Brain Collection obtained at autopsy with postmortem intervals of less than 4 hours were prepared for electron microscopic analysis according to standard techniques. The caudate nucleus and the putamen were similar in terms of the proportions of synaptic subtypes, the lengths of synaptic subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 89 publications
0
17
0
Order By: Relevance
“…Qualitative electron microscopic observations of either Golgi‐impregnated spidery neurons or ChAT‐immunoreactive cells in the primate dorsal striatum have revealed that ChIs receive symmetric and asymmetric synaptic inputs from morphologically heterogeneous terminal boutons indicative of diverse sources (Fig. ) . In a recent quantitative study, we demonstrated that 60% of all terminals in contact with ChIs in the monkey postcommissural putamen are GABAergic, while about 20% are putatively glutamatergic (asymmetric synapses/GABA‐negative), and the remaining 20% are of unknown chemical phenotype (symmetric synapses/GABA‐negative) (Fig.…”
Section: Synaptic Regulation Of Striatal Chismentioning
confidence: 89%
“…Qualitative electron microscopic observations of either Golgi‐impregnated spidery neurons or ChAT‐immunoreactive cells in the primate dorsal striatum have revealed that ChIs receive symmetric and asymmetric synaptic inputs from morphologically heterogeneous terminal boutons indicative of diverse sources (Fig. ) . In a recent quantitative study, we demonstrated that 60% of all terminals in contact with ChIs in the monkey postcommissural putamen are GABAergic, while about 20% are putatively glutamatergic (asymmetric synapses/GABA‐negative), and the remaining 20% are of unknown chemical phenotype (symmetric synapses/GABA‐negative) (Fig.…”
Section: Synaptic Regulation Of Striatal Chismentioning
confidence: 89%
“…To our knowledge, this is the first quantitative electron microscopic analysis using stereologic techniques comparing the synaptic organization of the patch matrix compartment of the striatum, in any species. There are differences in striatal anatomy among different species even among mammals, including differences in synaptic organization (Dube et al, 1988; Sadikot et al, 1992b; Smith et al, 1994; Roberts et al, 1996). Although the results of the present study may apply to the ultrastructure of other species, particularly non‐human primates, definitive experiments would be needed to demonstrate similarities or differences.…”
Section: Discussionmentioning
confidence: 99%
“…In various mammalian species (Pasik et al, 1976; Chung et al, 1977; Hassler et al, 1978; Roberts et al, 1995a, b) including human (Roberts et al, 1996), the majority of synapses present in the striatum form asymmetric synapses, characteristic of excitatory synaptic transmission. The terminals forming these synapses originate predominantly from neurons in the cortex (Kemp and Powell, 1971a, b, c), with less extensive inputs arising from the thalamus (Kemp and Powell, 1971a, b, c; Sadikot et al, 1992a, b; Smith et al, 1994) and the raphe (LaVoie and Parent, 1990).…”
mentioning
confidence: 99%
“…Other studies have compared High and Low VCM rats as far as neuronal spine size and density. In the mammalian striatum the most prevalent neuronal subtype is the medium spiny projection neuron and the majority of striatal synapses are formed with these spines (Chung, Hassler, & Wagner, 1977;Hassler, Chung, Rinne, & Wagner, 1978;Kemp & Powell, 1971a, 1971bRoberts, Gaither, Peretti, Lapidus, & Chute, 1996). Thus, changes in spine size or density could have profound effects on striatal synaptic organization.…”
Section: Previous Morphological Studiesmentioning
confidence: 99%